PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP KINERJA PEMERINTAH DESA (Studi Empiris Pada Desa di Kabupaten Kepulaun Meranti) - Findayani Igus Tusanti; Basri Mutia Yesi; Zarefar Arumega (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to prove empirically the influence of the principles of goodgovernance on the performance of the village government. The population of this study isthe village government in the Kepulauan Meranti Regency. The research sample usedpurposive sampling, namely all villages in Tebing Tinggi District, Tebing Tinggi Baratand Rangsang Barat District of Meranti Islands, which amounted to 31 villages. Datawas collected through surveys by distributing questionnaires, where the respondents werevillage heads, village secretaries, heads of financial affairs and 124 general affairsheads. The analytical method used in this study is multiple regression analysis. Theanalytical tool used is Statistical Product and Service Solution (SPSS) version 23.0. Thevariables used are transparency, accountability, community participation and justice asindependent variables. While the performance of the village government as the dependentvariable. The results of the study show that transparency, accountability, communityparticipation and justice have a positive effect on the performance of the villagegovernment.Keywords : Transparency, Accountability, Community Participation, Justice, VillageGovernment Performance.